Modelling Green Technology Researchers In Opportunity Creation - Ahamat, Amiruddin; Ahamad, Suraya; Rajiani, Ismi; Miskun, Muhammad Fahmi; Huslan, Muhammad Amir Afham (UTeM, 2020)
Entrepreneurship and opportunity creation are closely related survivability among entrepreneurs. Most of researchers have debated whether entrepreneurial opportunities are discovered or created. Many researchers have often overlooked the importance of the various factors that stimulate and shape the process of entrepreneurial opportunity. The objective of the study is to explore the oppo~tunitiest hat green technology might bring to entrepreneurs by complying with new business success factors particularly Malaysian academic and industrial researchers. The research contains six themes of opportunity creation on green technology researchers in Malaysia influenced by three main factors; individual cultural, institutional cultural and sosiocultural. The primary source of empirical data for this study is developed through a series of qualitative interviews. Adopting a case study method, this paper includes in-depth interviews with fifteen green technology researchers in Malaysia to understand how they shape their research's to create potential business opportunities. This research, there are two case study which is green technology researchers in academic field and green technology researchers in industrial field. conceptual framework is developed, based on previous literatures and existing adoption models were discussed and merged. The study employs Dubin's Theory, theory-building framework to propose a model of opportunity creation on green technology researchers. The findings of this study includes enriching the body of entrepreneurship knowledge. Finally, some recommendations are made to develop more research on opportunity creation on green technology researchers in Malaysia. For further research, understanding of the opportunity creation must be more in-depth for strengthening findings obtained. The research needs to study on wider scope which is respondents from other institution and a larger sample to further strengthen the reliability of the research.